1976
DOI: 10.1080/00288233.1976.10420970
|View full text |Cite
|
Sign up to set email alerts
|

The tenderness of meat of several breeds of cattle raised under New Zealand pastoral conditions

Abstract: Three experiments are reported in which the tenderness of meat from 171 steers of 6 breeds (Angus, Friesian, Jersey, Ayrshire, Galloway, and Red Poll) was measured as shear forces. Generally, differences between breeds for meat tenderness were not statistically significant, although the meat of Jersey cattle was significantly more tender than that of some o~he! breeds in one experiment, an effect which is consistent with overseas evidence. Some. significant breed effects were shown on the way in which post-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…23 The mean lipid content of the LTL muscle (Table 3) did not differ between the two breeds or between the three feed types, but the level at about 10% of muscle weight was appreciably above values reported for this muscle from carcasses at normal commercial weights. 24 The RSD value of 32.8 g kg À1 in Table 3 and the plots in Fig 1 indicate that the intramuscular lipid levels varied widely around the means with a range from about 3% to 18% of muscle weight. Similar mean values for concentrate-fed Japanese Black cattle at a carcass weight of 332 kg have been reported, 25 but values were signi®cantly lower for other breeds in their trial when comparisons were made at the same carcass weight.…”
Section: Resultsmentioning
confidence: 86%
“…23 The mean lipid content of the LTL muscle (Table 3) did not differ between the two breeds or between the three feed types, but the level at about 10% of muscle weight was appreciably above values reported for this muscle from carcasses at normal commercial weights. 24 The RSD value of 32.8 g kg À1 in Table 3 and the plots in Fig 1 indicate that the intramuscular lipid levels varied widely around the means with a range from about 3% to 18% of muscle weight. Similar mean values for concentrate-fed Japanese Black cattle at a carcass weight of 332 kg have been reported, 25 but values were signi®cantly lower for other breeds in their trial when comparisons were made at the same carcass weight.…”
Section: Resultsmentioning
confidence: 86%
“…Nonetheless, the Jersey could be used in this role if the economics of its use showed that it was profitable to do so. Jersey meat is superior in tenderness (Purchas & Barton 1976), and this advantage could make it an attractive meat in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Branaman et al (1962) found no difference in shear-force values, sensory panel ratings for tenderness, aroma, flavour of fat and texture of lean between beef and dairy-type cattle. Purchas & Barton (1976) reported Warner-Bratzler shear force measurements of tenderness of meat from three experiments involving 171 steers of six breeds (including Angus, Friesian and Jersey) raised under New Zealand pastoral conditions. Differences in tenderness were only recorded in one experiment where beef from Jersey steers had a significantly lower shear force than beef from the Angus and New Zealand Friesian steers.…”
Section: Meat Qualitymentioning
confidence: 99%